LRBA Deficiency in a Patient With a Novel Homozygous Mutation Due to Chromosome 4 Segmental Uniparental Isodisomy - Soler-Palacín, Pere; Garcia-Prat, Marina; Martín-Nalda, Andrea; Franco-Jarava, Clara; Rivière, Jacques G.; Plaja, Alberto; Bezdan, Daniela; Bosio, Mattia; Martínez-Gallo, Mónica; Ossowski, Stephan; Colobran, Roger (Frontiers in Immunology, 2018)
LRBA deficiency was first described in 2012 as an autosomal recessive disorder caused by biallelic mutations in the LRBA gene (OMIM #614700). It was initially characterized as producing early-onset hypogammaglobulinemia, autoimmune manifestations, susceptibility to inflammatory bowel disease, and recurrent infection. However, further reports expanded this phenotype (including patients without hypogammaglobulinemia) and described LRBA deficiency as a clinically variable syndrome with a wide spectrum of clinical manifestations. We present the case of a female patient who presented with type 1 diabetes, psoriasis, oral thrush, and enlarged liver and spleen at the age of 8 months. She later experienced recurrent bacterial and viral infections, including pneumococcal meningitis and Epstein Barr viremia. She underwent 2 consecutive stem cell transplants at the age of 8 and 9 years, and ultimately died. Samples from the patient and her parents were subjected to whole exome sequencing, which revealed a homozygous 1-bp insertion in exon 23 of the patient’s LRBA gene, resulting in frameshift and premature stop codon. The patient’s healthy mother was heterozygous for the mutation and her father tested wild-type. This finding suggested that either one copy of the paternal chromosome 4 bore a deletion including the LRBA locus, or the patient inherited 2 copies of the mutant maternal LRBA allele. The patient’s sequencing data showed a 1-Mb loss of heterozygosity region in chromosome 4, including the LRBA gene. Comparative genomic hybridization array of the patient’s and father’s genomic DNA yielded normal findings, ruling out genomic copy number abnormalities. Here, we present the first case of LRBA deficiency due to a uniparental disomy (UPD). In contrast to classical Mendelian inheritance, UPD involves inheritance of 2 copies of a chromosomal region from only 1 parent. Specifically, our patient carried a small segmental isodisomy of maternal origin affecting 1 Mb of chromosome 4.